P338 effectiveness and safety of biological therapies in elderly inflammatory bowel diseases patients results from a multi center study of Geteccu. (27th May 2021) - Suarez Ferrer, C J; Mesonero, F; Caballol, B; Saiz Chumillas, R; Bastón-Rey, I; Rubin de Celix, C; Melcarne, L; Caballero Mateos, A; Calafat, M; Alonso Galan, H; Vega Villaamil, P; Castro Senosiain, B; et al.
Abstract: Background: Biological drugs are being increasingly used for the treatment of inflammatory bowel diseases (IBD) in elderly patients. Despite the particular characteristics of this population subgroup, the efficacy and safety of these treatments in real clinical practice is poorly evaluated. Methods: Retrospective and multicenter study of GETECCU, carried out in 28 Spanish hospitals. Patients with IBD who started biological treatment (Infliximab, Adalimumab, Golimumab, Ustekinumab or Vedolizumab) aged 65 years or older were included. Efficacy (clinical- at the criteria of the responsible physician-, biochemical and endoscopic) was assessed at 12-14 weeks and at 52 weeks of treatment. Adverse effects such as tumors or serious infections were also recorded. Results: A total of 570 patients were included, baseline characteristics are shown in Table 1. Biologics used were: Infliximab (214, 37.5%), Adalimumab (167, 29.3%), Golimumab (16, 2.8%), Ustekinumab (73, 12.8%) and Vedolizumab (100, 17.5%). After 12-14 weeks of treatment, in 38.7% (220) of the cases clinical remission had been achieved and in 47.7% (270) there was clinical response without remission. However, 80 patients (13.9%) had no response, resulting in treatment discontinuation due to primary failure. At week 52, only 379 patients (66.5%) continued on biological treatment: 216 (57%) were in clinical remission (216, 57.0%) while 129 (34%) had response without remission and 34 (9%)had no response. In addition, 119 patients (21%) had an endoscopic study performed: 47 (39, 5%) presented with endoscopic remission, 38 (31, 9%) with mild activity, 28 (23, 5%) with moderate activity and 6, (5.1%) with severe activity. At the end of the follow-up, only 60% of the patients continued on biological treatment, being the reason for withdraw lack of efficacy or due to the report of adverse side effects. Regarding treatment safety in this population, 12.1% (68 patients) suffered an infectious complication with a microbiological diagnosis, requiring hospitalization in 62.1% of the cases. In addition, 39 patients (6.9%) were diagnosed with a tumor until the end of the follow-up, noting that 34.2% of the cases continued on biological therapy after the diagnosis. Likewise, in 25 patients (36.8%) this infection forced discontinuation of biological treatment. Finally, 10 patients stopped biological treatment due to a serious adverse reaction to it Conclusion: Response rates to biological treatment in elderly patients are similar to those described in the general population, with approximately one third of failures happening during the first year. However, a remarkable proportion of patients developed a serious adverse effect that could be related to treatment